2017
DOI: 10.1007/s10530-017-1513-2
|View full text |Cite|
|
Sign up to set email alerts
|

Management of invasive Phragmites australis in the Adirondacks: a cautionary tale about prospects of eradication

Abstract: Invasive plant management (largely mechanical and chemical) consumes an ever-increasing portion of budgets for land management organizations, but metrics of success, other than extent of areas treated or resources expended is rarely available. Here we assess success of managing 346 populations of invasive Phragmites australis (range 0.36-4134 m 2 ; cover 37-75%) in the Adirondack Park in upstate New York, USA. We began by treating 18 patches in 2010 using herbicide; gradually adding patches treated annually or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 121 publications
3
33
1
Order By: Relevance
“…Knowing the environmental circumstances that promote restoration success can help inform this decision‐making and allow for the most cost‐effective management. Our multi‐site study found wide variability in Phragmites management outcomes and native plant recovery, which indicates success in the restoration of Phragmites ‐invaded wetlands is highly context dependent, a finding consistent with studies in other regions of North America (Carlson et al, ; Hazelton, ; Quirion et al, ). We found that site hydrology played an important role in determining outcomes, but there were likely other unmeasured factors that contributed to divergent results such as landscape setting, site history, and age of invasion, which should be further explored.…”
Section: Resultssupporting
confidence: 88%
“…Knowing the environmental circumstances that promote restoration success can help inform this decision‐making and allow for the most cost‐effective management. Our multi‐site study found wide variability in Phragmites management outcomes and native plant recovery, which indicates success in the restoration of Phragmites ‐invaded wetlands is highly context dependent, a finding consistent with studies in other regions of North America (Carlson et al, ; Hazelton, ; Quirion et al, ). We found that site hydrology played an important role in determining outcomes, but there were likely other unmeasured factors that contributed to divergent results such as landscape setting, site history, and age of invasion, which should be further explored.…”
Section: Resultssupporting
confidence: 88%
“…The tissue chemistry of Phragmites and its extensive production alters nutrient pools 21 and availability in soils 16,18 . Together with its negative effects on ecology, Phragmites can impose considerable financial loss 22 . For example, invasive species management costs about $25 billion/year in the USA 23 .…”
mentioning
confidence: 99%
“…Current methods to control Phragmites invasions are aimed at eradication of existing populations, which are effective only in short term 31 . The recent study raises the question about the efficacy of managing large populations invaded by Phragmites through the method 22 . Generally, Phragmites populations can be treated using herbicide applications in combination with cutting, burning and covering with plastic 32 .…”
mentioning
confidence: 99%
“…Most studies that used herbicide report success in reducing the abundance of P. australis locally, but none suggest eradication was achieved. Some report short-term reductions in P. australis, and most caution that repeated control measures are needed to suppress re-growth (e.g., Lombard et al 2012;Quirion et al 2017). Fewer suggest that herbicide application led to the recovery of native vegetation.…”
mentioning
confidence: 99%
“…Ideally, recovery should target a vegetation community that resembles the community present in equivalent edaphic and hydrologic conditions where P. australis never invaded (i.e., the reference condition, sensu Stoddard et al 2006). Management outcomes for P. australis suppression techniques have received extensive study (e.g., Farnsworth and Meyerson 1999;Ailstock et al 2001;Derr 2008;Mozdzer et al 2008;Lombard et al 2012;Rapp et al 2012;Hunt et al 2017;Quirion et al 2017;Zimmerman et al 2018;Judd and Francoeur 2019;Rohal et al 2019a, b). Yet there are inconsistencies in the literature regarding information on baseline conditions, experimental controls, or adequately characterized recovery targets, making differences in outcomes difficult to reconcile.…”
mentioning
confidence: 99%